Nilai-nilai Pendidikan Karakter dalam Novel Rumah tanpa Jendela Karya Asma Nadia - Putri, Nelvi; Asri, Yasnur; Nurizzati, Nurizzati (Universitas Negeri Padang, 2013)
The purpose of this study is describe the values of character education which is contained in the novel of Asma Nadia â€œRumah Tanpa Jendelaâ€ such as : (1) loving god and truth. (2) responsibility, discipline, and self independent. (3) respect and courtesy. (4) affection, care, and teamwork. (5) self-comfident, creative and never give up. (6) fair and spirit leadership. (7) nice and humble, (8) tolerance and peace. ThisÂ is a kind of qualitative research by using descriptive method which can be used to describe data in the novel of Asma Nadia â€œRumahTanpa Jendelaâ€. The steps in analyzing the data is First, describe the data which is related to the values of character education. Second, interprete the data that have been analyzed. Third, divide theÂ data according to the values of character education. Fourth, conclude the result of the reseach.